2023
DOI: 10.1029/2022jg007287
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Summer Nitrogen Fixation by the Kuroshio Intrusion in the East China Sea and Southern Yellow Sea

Abstract: The western boundary currents are characterized by abundant diazotrophs including Trichodesmium, which may fuel N2 fixation when they intrude into marginal seas. The Kuroshio, a western boundary current in the North Pacific, flows into the East China Sea (ECS) and southern Yellow Sea (SYS), which transports abundant Trichodesmium and diatom‐diazotroph associations (DDAs). Additionally, low nitrogen:phosphorus (N:P) ratio and relatively abundant dissolved iron have been observed in the offshore ECS because of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 75 publications
3
8
1
Order By: Relevance
“…Indeed, we found similar N 2 xation rates within the cyclonic and anticyclonic eddies, with a trend to even higher rates, particularly with depth for the anticyclonic core (Table S1). This shows the overall importance of trapping eddies in supporting N 2 xation in one of the world's most mesoscale active regions, raising questions about their impact on other western boundary currents with similar observations 20,21 .…”
Section: Gulfsupporting
confidence: 53%
“…Indeed, we found similar N 2 xation rates within the cyclonic and anticyclonic eddies, with a trend to even higher rates, particularly with depth for the anticyclonic core (Table S1). This shows the overall importance of trapping eddies in supporting N 2 xation in one of the world's most mesoscale active regions, raising questions about their impact on other western boundary currents with similar observations 20,21 .…”
Section: Gulfsupporting
confidence: 53%
“…Here, we show that not only was the absolute flux of newly fixed N greater in shelf waters, but the relative contribution of diazotrophs to community N turnover was higher as well (Table S2 and Figure S8 in Supporting Information ), suggesting that diazotrophic contributions are important in supporting productivity on the shelf. Assessing diazotrophic contributions and their physicochemical drivers in this system has bearing not only on the regional N budget, but on our understanding of N 2 fixation in continental shelf systems globally, particularly those impacted by western boundary currents (e.g., Jiang et al., 2023; Marshall et al., 2023) where diazotrophy has been observed for decades (e.g., Prufert‐Bebout et al., 1993; Saino & Hattori, 1978). Our findings call for greater focus on shelf environments as regions of N 2 fixation and contributors to the global N budget, and for a paradigm shift regarding the relative importance of N 2 fixation in fueling productivity near the coast.…”
Section: Discussionmentioning
confidence: 99%
“…The Changjiang Estuary (CE) and adjacent East China Sea (ECS) and southern Yellow Sea are primarily characterized by eutrophic, low-salinity Changjiang Diluted Water (CDW) and oligotrophic, warm, saline nearshore Kuroshio Branch Current (NKBC; modified Kuroshio subsurface water) and Taiwan Warm Current (TWC; a mixture of the intruded Kuroshio water and the Taiwan Strait water) ( Figure 1A ). Although nitrogen repletion and low temperature (<20°C) in the CE restrain the growth of Trichodesmium and N 2 fixation ( Zhang et al, 2012 ; Jiang et al, 2018 , 2023 ), relatively high NFR (3.37 nmol N L −1 d −1 ) was observed during spring ( Lin et al, 2013 ), likely contributed by unicellular diazotrophs, particularly heterotrophic diazotrophs. Conversely, abundant Trichodesmium ( Jiang et al, 2018 , 2019 ) and extremely high NFR (up to 62 nmol N L −1 d −1 ; Zhang et al, 2012 ; Shiozaki et al, 2015 ; Wu et al, 2018 ) occurred in the Kuroshio, which largely enhanced N 2 fixation in the ECS ( Jiang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although nitrogen repletion and low temperature (<20°C) in the CE restrain the growth of Trichodesmium and N 2 fixation ( Zhang et al, 2012 ; Jiang et al, 2018 , 2023 ), relatively high NFR (3.37 nmol N L −1 d −1 ) was observed during spring ( Lin et al, 2013 ), likely contributed by unicellular diazotrophs, particularly heterotrophic diazotrophs. Conversely, abundant Trichodesmium ( Jiang et al, 2018 , 2019 ) and extremely high NFR (up to 62 nmol N L −1 d −1 ; Zhang et al, 2012 ; Shiozaki et al, 2015 ; Wu et al, 2018 ) occurred in the Kuroshio, which largely enhanced N 2 fixation in the ECS ( Jiang et al, 2023 ). These results showed that NFR in the ECS was highly associated with Trichodesmium , probably indicating a high contribution of Trichodesmium to N 2 fixation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation